Beneficial effect of Brahmi Ghrita on learning and memory in normal rat - Yadav, Kapil Deo (Ayu, 2014)
BACKGROUND: Learning, the process of acquiring memory such as behavioral change due to previous experiences and most intensively studied subjects in the field of neuroscience through various approaches to understand the mechanisms. Brahmi Ghrita (BG) was claimed for the treatment of learning and memory disorders in human being. AIM: To assess learning and memory activity of BG in normal rats. MATERIALS AND METHODS: For this study, 24 rats were taken and divided into four groups (six in each). First group served as the control group, second and the third group as BG treated groups (400 and 800 mg/kg, p. o.) and the fourth group as standard drug (piracetam) 500 mg/kg, p.o. treated group. Learning and memory, activity of BG was evaluated in normal rats, using elevated maze plus and passive avoidance test. RESULTS: BG and piracetam treated rats demonstrated a significant decrease in transfer latency in modified elevated plus maze test and increase in step through latency in passive avoidance test compared with control rats in a dose dependent manner. It may be due to increase in learning and memory. It was also reported that prolonged use of Bacopa monneri (L.) Pennell causes elevation of cerebral glutamic acid and transient increase in gamma aminobutaric acid, which may be helpful in the process of learning. CONCLUSION: Brahmi Ghrita enhances learning and memory as analogous to standard drug (piracetam) in normal rats.